IMPLEMENTATION OF THE NAIADES ACTION PROGRAMME FOR THE PROMOTION OF INLAND WATERWAY TRANSPORT - Sosedova, Jarmila; Slesinger, Jan (Doprava a spoje, 2011)
In January 2006 the European Commission adopted the Communication for the promotion of inland waterway transport. The NAIADES Action Programme is intended for the period 2006-2013 and focuses on five strategic areas for a comprehensive Inland Waterway Transport policy such as market, fleet, jobs and skills, image and infrastructure. In December 2007 the European Commission presented the first progress report that was made in implementing the so-called NAIADES programme which is aimed at the promotion of inland waterway transport in Europe. Registers progress in a broad range of areas, including initiatives that have been launched to improve market conditions, to modernise the fleet, to make the profession more attractive, and to improve waterway infrastructure. In April 2011 the NAIADES progress report was published by the European Commission. The NAIADES progress report has covered the period since 2006 so far. The report takes stock of the implementation of NAIADES and also identified where further action is required.